Avaliação microbiológica de alfaces (Lactuva sativa) obtidas em cultivos tradicional, orgânico e hidropônico - Gomes Neto, Nelson Justino (2011)
Lettuce (Lactuva sativa) is the increased consumption of leafy vegetables in Brazil, however may be associated with the transmission of pathogenic microorganisms to human. The present study was to evaluate the microbiological quality of samples of curly lettuce variety, obtained from the traditional farming systems, organic and hydroponic sold in the city of João Pessoa, Paraiba, and verify the effectiveness of washing with sterile distilled water and sodium hypochlorite sanitizers 150 ppm and 1% acetic acid to reduce their bacterial load. We analyzed 60 samples for each cropping system, equally distributed between the bacteriological and parasitological tests, totaling 180 specimens. For bacteriological analyses, the samples were subjected to the determination of most probable number (MPN) of total and thermotolerants coliforms, total counts of mesophilic aerobic microorganisms and Salmonella sp. In holding the tests using spontaneous sedimentation parasitological, were surveyed primary structures of protozoa and helminthes. Salmonella sp. was not detected in the samples analyzed, regardless of cropping system. However, the results showed high contamination by mesophilic aerobic bacteria and total coliforms in samples of conventionally grown and organic, which also showed fecal coliforms counts higher recommended by the Brazilian legislation in 66% and 80% of the samples, respectively. For samples of traditional and organic crops was also observed high frequency of intestinal parasites, including pathogenic species Taenia sp. and Entamoeba histolytica. In contrast, only 20% of hydroponic lettuce samples were contaminated with intestinal parasites. The cleaning with sterile water was sufficient to reduce the bacterial load to safe levels only in hydroponic samples, already tested sanitizers were effective in reducing bacterial counts in all crops.